Effect of process intensifying parameters on the hydrodynamic cavitation based degradation of commercial pesticide (methomyl) in the aqueous solution - Raut-Jadhav, Sunita; Saini, Daulat; Sonawane, Shirish; Pandit, Aniruddha (Ultrasonics Sonochemistry, 2016)
Methomyl, a carbamate pesticide, is classified as a pesticide of category-1 toxicity and hence shows harmful effects on both human and aquatic life. In the present work, the degradation of methomyl has been studied by using hydrodynamic cavitation reactor (HC) and its combination with intensifying agents such as H2O2, fenton reagent and ozone (hybrid processes). Initially, the optimization of operating parameters such pH and inlet pressure to the cavitating device (circular venturi) has been carried out for maximizing the efficacy of hydrodynamic cavitation. Further degradation study of methomyl by the application of hybrid processes was carried out at an optimal pH of 2.5 and the optimal inlet pressure of 5 bar. Significant synergetic effect has been observed in case of all the hybrid processes studied. Synergetic coefficient of 5.8, 13.41 and 47.6 has been obtained by combining hydrodynamic cavitation with H2O2, fenton process and ozone respectively. Efficacy of individual and hybrid processes has also been obtained in terms of energy efficiency and extent of mineralization. HC + Ozone process has proved to be the most effective process having highest synergetic coefficient, energy efficiency and the extent of mineralization. The study has also encompassed the identification of intermediate by-products generated during the degradation and has proposed the probable degradation pathway. It has been conclusively established that hydrodynamic cavitation in the presence of intensifying agents can effectively be used for complete degradation of methomyl. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Advanced Oxidation Processes (AOPs); Hydrodynamic cavitation; Methomyl; Synergetic coefficient; Venturi

Intensification of degradation of methomyl (carbamate group pesticide) by using the combination of ultrasonic cavitation and process intensifying additives - Raut-Jadhav, Sunita; Pinjari, Dipak V.; Saini, Daulat R.; Sonawane, Shirish H.; Pandit, Aniruddha B. (Ultrasonics Sonochemistry, 2016)
In the present work, the degradation of methomyl has been carried out by using the ultrasound cavitation (US) and its combination with H2O2, Fenton and photo-Fenton process. The study of effect of operating pH and ultrasound power density has indicated that maximum extent of degradation of 28.57% could be obtained at the optimal pH of 2.5 and power density of 0.155 W/mL. Application of US in combination with H2O2, Fenton and photo-Fenton process has further accelerated the rate of degradation of methomyl with complete degradation of methomyl in 27 min, 18 min and 9 min respectively. Mineralization study has proved that a combination of US and photo -Fenton process is the most effective process with maximum extent of mineralization of 78.8%. Comparison of energy efficiency and cost effectiveness of various processes has indicated that the electrical cost of 79892.34 Rs./m(3) for ultrasonic degradation of methomyl has drastically reduced to 2277.00 Rs./m(3), 1518.00 Rs./m(3) and 807.58 Rs./m(3) by using US in combination with H2O2, Fenton and photo-Fenton process respectively. The cost analysis has also indicated that the combination of US and photo-Fenton process is the most energy efficient and cost effective process. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Fenton; Hydrogen peroxide; Methomyl; Photo-Fenton; Synergistic coefficient; Ultrasound cavitation